2021
DOI: 10.1108/jd-07-2020-0115
|View full text |Cite
|
Sign up to set email alerts
|

Engaging interaction and long-term engagement with WhatsApp in an everyday life context: exploratory study

Abstract: PurposeThe aim of this exploratory study is to analyze if the most used factors related to the engaging interaction and long-term engagement with online applications can be applied to WhatsApp in a context of everyday life in Madrid and to investigate what parameters would best describe the engagement with WhatsApp in this context.Design/methodology/approachA qualitative method was employed to explore the cognitive, emotional and behavioral factors that mainly comprise the experience of a user with an online a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 101 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…Studies have shown instances where unverified messages are inflammatory (Mohit, 2012;Gong et al, 2018;Thrassou et al, 2020). This provocative, exaggerated and unverified information often becomes the root cause of social unrest, and even can cause mob lynching, as is evident from other studies (Choliz, 2012;Supriya, 2012;Chaudhuri et al, 2013a;Sakka et al, 2021;Martinez-Comeche and Ruthven, 2021). Mob lynching has become a new type of offence, which is done when someone hurts a community's feelings.…”
Section: Literature Reviewmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies have shown instances where unverified messages are inflammatory (Mohit, 2012;Gong et al, 2018;Thrassou et al, 2020). This provocative, exaggerated and unverified information often becomes the root cause of social unrest, and even can cause mob lynching, as is evident from other studies (Choliz, 2012;Supriya, 2012;Chaudhuri et al, 2013a;Sakka et al, 2021;Martinez-Comeche and Ruthven, 2021). Mob lynching has become a new type of offence, which is done when someone hurts a community's feelings.…”
Section: Literature Reviewmentioning
confidence: 91%
“…People normally do not verify the information disseminated through IM platforms, but they are influenced to react to such unverified information, which may cause harm to the society (Udem et al, 2020;Martinez-Comeche and Ruthven, 2021).…”
Section: Dark Side Of Instant Messagingmentioning
confidence: 99%
“…WhatsApp is a smartphone application that can be operated on most devices and operating systems currently available (Bouhnik and Deshen, 2014; Jailobaev et al , 2021). Although it is considered a form of mobile instant messaging (Church and Oliveira, 2013; Padmavathy et al , 2018; Cruz-Cárdenas et al , 2019; Martinez-Comeche and Ruthven, 2021), it is also technically identified as a social networking application, which facilitates people wider access to information (Bouhnik and Deshen, 2014). WhatsApp provides a variety of functions, such as text messages, images, audio files, video files and links to web addresses (Church and Oliveira, 2013; Bouhnik and Deshen, 2014; Jailobaev et al , 2021) at low cost (Chaputula et al , 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Moreover, students derive academic advantages such as accessibility of learning materials, teacher availability and the continuation of learning beyond class hours (Bouhnik and Deshen, 2014). Meanwhile, in contrast, a study of WhatsApp use in everyday life in Madrid asserts that many participants think WhatsApp is frequently amusing; but find the repetitive process of checking for and replying to texts, without significant variation in conversation topics or participants, sometimes boring; and the overload of information stressful (Martinez-Comeche and Ruthven, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation